An Analysis of Common Errors in Conversation - Dimas Yoga Anggara; Irfan; Irham; Salmah Fikry; Yani Lubis (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This study aims to analyze the grammatical errors and to provide description of errors on speaking activities using simple present and present progressive tenses made by the second year students of English Education Department, Palangka Raya University. The subject for this study was 30 students. This research applied qualitative research to describe the types, source and causes of students’ errors taken from oral essay test which consisted of questions using the tenses of simple present and present progressive. The errors were indentified and classified according to Linguistic Category Taxonomy and Richard’s classification, well as the possible sources and causes of errors. The findings showed that the errors made by students were in 6 aspects; errors in production of verb groups, errors in the distribution of verb groups, errors in the use of article, errors in the use of preposition, errors in the use of questions and miscellaneous errors. In regard to resource and causes, it was found that intra-lingual interference was the major source of errors (82.55%) where overgeneralization took place as the major cause of the errors with total percentage of 44.71%.